Cycling for a mission - The Star, Y.P sivam (2012)
IT WAS a new experience for athlete K. Ganthimathi and karate exponent M. Yokanathini during the Cycle to Class programme, organised by Faculty of Modern Languages and Communication (FMLC), at Universiti Putra Malaysia (UPM) in Serdang recently.